Simulation studies of the solvent diethylamine for post-combustion CO2 capture at the WACEM cement manufacturing plant in southern Togo at Tabligbo - Koevidjin, Solagnon Edoh; Nougbléga, Yawovi; Amouzouvi, Yawovi Mignanou; Dzagli, Milohum Mikesokpo; Mohou, Messanh Agbéko (Edelweiss Applied Science and Technology, 2025)
Industrial CO2 emissions continue to rise despite global reduction efforts, driving climate change and global warming. Post-combustion carbon capture using aqueous diethylamine (DEA) is a promising strategy to mitigate these emissions. This study aims to simulate CO2 absorption from the Western African Cement (WACEM) industry’s flue gases using the Hysplit model. The tray column's key parameters, the gas-liquid mixture's thermophysical properties, and the treated emissions' composition were investigated. Results indicate optimal CO2 absorption occurs when the flue gas mass flow rate does not exceed 12.5% of the liquid mixture entering the column. The process is most effective at a DEA flow rate of 250 L/h, with a furnace temperature of 160°C and a pressure of 17 bars. These findings provide valuable insights for policymakers and industry stakeholders in optimizing post-combustion carbon capture for emission reduction.